Screening on cytotoxic and antidiabetic activity from various local ulam - Fatimah, Mohamad Yakup. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Many medicinal plants have been used in traditional medicines for their antidiabetic properties without any scientific support and pharmacological evidence. The aqueous extract of ulam has been taken to evaluate the hyperglycemic activity in hyperglycemic hamster (after sugar induced). A single oral administration of 5OOmglkg aqueous extract led to lowering ofblood glucose level in hyperglycemic hamster. The high average fall of 38.67% in control hamster and 42.26% in hyperglycemic hamster was observed after 1,4, and 8 hour. The findings from this study suggest that the aqueous extract ofIpomoea aquatica could be prescribed as adjunct to dietary therapy and drug treatment for controlling diabetes mellitus.